Country‐specific participation patterns in transnational governance initiatives on sustainability [dataset]: preliminary insights and research agenda - Tosun, Jale; Levario Saad, Emiliano; Glückler, Johannes; Irigoyen Rios, Alejandra; Lehmann, Rosa (Universität, 2023)
Contains data on transnational governance initiaties on sustainability. The data is self coded on the based of information provided by the tansnational governance initiatives on their respective websites.
Gesehen am 20.11.2023
Keywords: Forschungsdaten; Datenbank